Rate of return and risks of an investment in Lao Securities eXchange (LSX) by using CAPM - LATHILATH, Ounla; KEOBOULAPHETH , Soulideth; PHOUNNALY, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The decision to invest in the investor's securities is to make profits from the difference in stock trading, and there is confidence that businesses can make good profits that will affect stock prices and dividends. Investing in the securities market is a high-risk investment as investors will need to study the data carefully to get the expected return. Therefore, when considering investing in a portfolio that is popular around the world by using Capital Asset Pricing Model (CAPM). Which model for Analysis risks and rate of return of an investment in Securities exchange. In the rate of return and risks of an investment of Lao Securities eXchange (LSX) has the purpose in 1) . comparing risks and return of an investment in securities with risks and market return. 2). comparing actual return with expected returns by using CAPM and uses secondary data by considered the close of stock market index, LSX index and yield of 1-year bonds as the risk-free securities to investment decisions, the analysis was conducted for 11 stocks in LSX, include BCEL, EDL-GEN, LWPC, PTL, SVN, PCD, LCC, MHTL, LAT, VCL and LCLCO. Which data analysis from 2 January 2019 to 13 February 2020 (530 official working days). CAMP is used for analysing the data from the LSX. The results showed that the risk of all securities was higher than the risk market, except that MHTL securities was below than risk market. The EDL-GEN and LCLCO securities has beta coefficient of greater than 1 and there is a positive relationship. Which return rate of securities to change in line with return of market. The actual rate of return over the rate of expected return ( Undervalued). As the result, the investors should invest or buy such securities including BCEL, LWPC, LCC and LCLCO according to their undervalued stock and in the future such securities are likely to Adjust prices higher, while The actual rate of return is less than the rate of expected return ( Overvalued) to the investor should not made decision to invest or sell the securities including EDL-GEN, PTL, SVN, PCD, MHTL, LAT and VCL according to their overvalued stock and in the future such securities are likely to Adjust prices down.